A review on oxygen storage capacity of CeO2-based materials: Influence factors, measurement techniques, and applications in reactions related to catalytic automotive emissions control - Li, Ping; Chen, Xiaoyin; Li, Yongdan; Schwank, Johannes W. (Catalysis today, 2019)
[Display omitted] •OSC is classified into two categories: total and dynamic.•Elemental doping, active component loading, geometrical, and environmental conditions that affect OSC are reviewed.•Measuring techniques and conditions that affect the OSC amount are also discussed.•Typical catalytically reactions related to the role of OSC in automotive emissions control are focused. CeO2 is widely used as a catalyst support component due to its redox property of oxygen storage and release. This unique feature, which is usually referred to as “oxygen storage capacity” (OSC), can be quantitatively evaluated by different methods and techniques. Since the oxygen release benefits oxidation reactions, catalytic activity can be correlated with OSC. The measured amount of OSC can be influenced by a number of factors, such as the nature of the reducing agent, the conditions of reducing gas flow and operation temperature, the aging, the composition, and physical and geometric properties of CeO2-based materials, and the type of analytical technique used. Therefore, these influencing factors include, but are not limited to, the use of H2 or CO as reducing agent, continuous or pulsed feed of reducing agent, the presence of other elements in the CeO2 structure, particle size and surface area, supported catalyst components and aging, etc. This review paper focuses on the measurement of OSC, the effect of influencing factors, and the role of OSC in the typical reactions that occur in automotive emission control like oxidation, NO reduction, water gas shift, and reforming reactions. Furthermore, this review addresses the reactions in which the catalytic activity can be correlated with OSC.